DEFA after East Germany - Wagner, Brigitta B., 1978- (Rochester, New York : Camden House, 2014)
"In the late 1980s and early 1990s, East Germany's DEFA filmmakers had a brief window in which to critique GDR society on either side of the Wende, the sweeping political turn that surrounded the fall of the Berlin Wall and the opening of the border. Building on the DEFA Film Library's retrospective Wende Flicks series and Indiana University's DEFA Project, this study examines the newly rediscovered filmic artifacts of this transitional cinema, introducing eighteen key films from 1988 to 1994 in essays by German scholars, film professionals, and cultural figures. Accompanying interviews and historical film reviews present a complex portrait of East German film art, its communist bloc influences, and its legacy for contemporary German film culture. The resulting anthology combines historical, autobiographical, cultural-political, and journalistic discourses to explore the tension between the hopes and frustrations these films express, the historical exigencies that overshadowed their production and reception, and the politics of their revival."--
Introduction: making history revisible / Brigitta B. Wagner -- Part I. Sketching DEFA's past and present. Thoughts for Indiana / Wolfgang Kohlhaase -- Not a bad heritage: an interview with Andreas Dresen / Brigitta B. Wagner -- Spectral images in the afterlife of GDR cinema / Barton Byg -- Part II. Film in the face of the Wende. The Wende in film / Knut Elstermann -- Between times: my experience as a director during the Wende / Peter Kahane -- "Look, people, look!": an interview with Eduard Schreiber / Peter Blank -- The theatricality of "shard films": an interview with Jorg Foth / Nicholas Sveholm -- Competing archives: intertextuality and Wende narrative in the "last films from East Germany" / Claudia Breger -- The state of being done: film at the end of the second world / Benjamin Robinson -- Part III. Migrating DEFA to the FRG. Cinema after the GDR's downfall: the story of Ö-Film / Katrin Schlosser and Frank Loprich -- When Berlin-Brandenburg met Kommerz-Keil: an interview with Klaus Keil / Brigitta B. Wagner -- Performing the GDR: the last DEFA generation and the tradition of theatricality / Johannes Von Moltke -- Surveillance states: structures of conspiracy in Wende cinema / Jennifer M. Kapczynski -- Cleansing the system: East German cinema repurposed / Brigitta B. Wagner -- Part IV. Archive and audience. Historical archaeology: curating the Wende Flicks series / Skyler J. Arndt-Briggs -- The DEFA Foundation, 2010: rediscover the past-support the future / Helmut Morsbach -- Activating an archive of inner perspectives: political education with DEFA films / Thomas Kruger -- Part V. Reception materials. Vorspiel (1987) / curated by Anne Jost-Fritz-- flüstern & SCHREIEN (1988) / curated by Michelle Sybert -- Coming Out (1989) / curated by Birgitta B. Wagner -- Leipzig im Herbst (1989) and Östliche Landschaft (1991) / curated by Peter Blank -- Die Architekten (1990) / curated by Tracy N. Graves -- Die Mauer (1990) / curated by Birgitta B. Wagner -- Letztes aus der DaDaeR (1990) / curated by Tracy N. Graves -- Der Tangospieler (1991) / curated by Nicholas Sveholm -- Verriegelte Zeit (1991) / curated by Birgitta B. Wagner -- Das Land hinter dem Regenbogen (1992) / curated by Troy Byler -- Verfehlung (1992) / curated by Wendy Westphal -- Stilles Land (1992) / curated by Birgitta B. Wagner -- Jana und Jan (1992) / curated by Olivia Landry -- Herzsprung (1992) / curated by Lisa Haegele -- Sammelsurium: Ein ostelbischer Kulturfilm (1992) / curated by Birgitta B. Wagner -- Miraculi (1992) / curated by Jordan Allen -- Burning Life (1994) / curated by Troy Byler -- The Schlöndorff Controversy (2008) / curated by Birgitta B. Wagner.
Includes bibliographical references (pages 333-336) and index.
Print version record.
JSTOR
Keywords: DEFA -- History; DEFA; Motion picture industry -- Germany (East) -- History; Motion pictures -- Germany (East) -- History; Motion pictures -- Germany -- History and criticism; Cinéma -- Industrie -- Allemagne (Est) -- Histoire; Cinéma -- Allemagne (Est) -- Histoire; Cinéma -- Allemagne -- Histoire et critique; PERFORMING ARTS -- Reference; PERFORMING ARTS -- Film & Video -- History & Criticism; Motion picture industry; Motion pictures; Germany; Germany (East); Filmbranschen -- historia; Film -- historia; Berlin Wall; Cinema; Cultural; DEFA; East Germany; Film Art; German Studies; Politics; Retrospective; Transition; Criticism, interpretation, etc; History